BANJARESE GREETINGS SYSTEM IN DISTRICT KAPUAS OF CENTRAL KALIMANTAN - Perdana, Indra; HP, Achmad (IJLECR (International Journal of Language Education and Cultural Review), 2015)
Research on the study of the use of greeting in Banjarese which stay in Kapuas District of Central Borneo.This Research focused to describe the greeting word used by the people, particularly the greeting word in Banjarese used by the first generetion in Kapuas. The research method used is descriptive qualitative. Data collection by observation with a look at, involved notes. Sources of research data used is the preference of all speech that is displayed by 1) Aged over 30 years, 2) Native language studied. 3) Knowing its own culture, 4) The Banjarese are the first generation derived from Banjarmasin, 5) The Banjarese who had lived in Kapuas. Based on this research shows 1) Greetings kinship to greet our parents (father + mother) → (+ Uma Abah); Greetings kinship parents to greet our father and mother (grandfather + grandmother) → (kai + nini); Greetings kinship to greet parents our grandparents are corrected; Greetings kinship to greet both parents protested was waring; Greetings kinship to say hello (brother + sister) → (kaka + ading). Greetings kinship to say hello if our children have children (grandchildren) → (grandchildren); Greetings kinship to say hello if we have children and grandchildren is a great-grandfather. And 2) The system of daily greeting, to call people who may be called ikam lifetime, lives. I use the word, unda to appoint themselves. As for honor or call older used the word pian, and said ulun to appoint its own self.